English Reading Materials in Non-Formal Education: A Need Analysis - Pratiwi, Ayu; Priyana, Joko (VELES Voices of English Language Education Society, 2024)
Conducting a needs analysis is imperative for customizing educational content to align with students' specific learning prerequisites, especially in the realm of reading skill development, which is acknowledged as a challenging domain. This study investigates into the necessity for tailored English reading materials within non-formal educational frameworks, with a focus on junior high students at the Gosmart Institution in Yogyakarta. Utilizing a combination of surveys and interviews, data was collected from 50 students, revealing a strong inclination towards vocabulary enhancement and the extraction of detailed information from texts as their primary learning objectives. The analysis uncovers students' difficulties with presentation activities, largely due to confidence issues, alongside a pronounced preference for reading materials enriched with illustrative and social media images. Additionally, the study points out the scarcity of authentic reading resources, which hampers the effectiveness of teaching strategies. The findings advocate for the integration of these insights into the development of English reading materials, proposing a targeted approach to ameliorate reading instruction and address the highlighted educational needs. This study underscores the importance of adapting educational resources to meet learner preferences and challenges, thereby enhancing the overall teaching and learning experience in reading skills development.